2008
DOI: 10.1007/s12088-008-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a bacterial strain isolated from the liver of a laboratory mouse as Microbacterium paraoxydans and emended description of the species Microbacterium paraoxydans Laffineur et al 2003

Abstract: A rod-shaped, Gram-positive bacterial strain, designated C57-33, was isolated from the liver of the laboratory mouse strain C57Bl/6J and characterised by a polyphasic approach. 16S rRNA gene sequence similarity placed strain C57-33 in the genus Microbacterium with Microbacterium paraoxydans CF36T as the next relative (99.9 % sequence similarity). Major fatty acids ai-C 15:0 , i-C 16:0 and ai-C 17:0 and peptidoglycan type B2β with ornithine as the diagnostic cell-wall diamino acid and glycolyl residues were in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The few earlier studies, including ours, on leaf associated hydrocarbon-utilizing bacteria (Buczolits et al, 2008;Al-Mailem et al, 2010;McGuinness and Dowling, 2011;Sorkhoh et al, 2011;Ali et al, 2012) were done on few plant species, a shortcoming which has been corrected in this work. In this context, although the culture based approach for bacterial counting reveals only a fraction of the values obtained by the direct and molecular approaches, we adopted the culture based technique because, in contrast to the others, it specifically counts hydrocarbon utilizing bacteria, and makes bacterial cultures available for further study.…”
Section: Discussionmentioning
confidence: 97%
“…The few earlier studies, including ours, on leaf associated hydrocarbon-utilizing bacteria (Buczolits et al, 2008;Al-Mailem et al, 2010;McGuinness and Dowling, 2011;Sorkhoh et al, 2011;Ali et al, 2012) were done on few plant species, a shortcoming which has been corrected in this work. In this context, although the culture based approach for bacterial counting reveals only a fraction of the values obtained by the direct and molecular approaches, we adopted the culture based technique because, in contrast to the others, it specifically counts hydrocarbon utilizing bacteria, and makes bacterial cultures available for further study.…”
Section: Discussionmentioning
confidence: 97%
“…Strains CC-SBCK-209 T , CC-12309 T and CC-5209 T exhibited polar lipid profiles consisting of the major components diphosphatidylglycerol, phosphatidylglycerol and an unknown glycolipid that showed identical behaviour during TLC analyses of the extracts of the three strains. These major polar lipids have been detected in numerous Microbacterium species (Zlamala et al, 2002;Rivas et al, 2004;Kim et al, 2005;Shivaji et al, 2007;Buczolits et al, 2008;Park et al, 2006) and they have also been listed in the emended description of the genus (Takeuchi & Hatano, 1998). In addition, in the extract from strain CC-SBCK-209 T , minor amounts of a second unknown glycolipid and two unknown phospholipids were detected (Fig.…”
mentioning
confidence: 85%
“…The quinone system of strain CC-5209 T comprised MK-13 (92 %) as the major compound, with minor amounts of MK-12 (4 %) and MK-14 (4 %). It can be assumed that examination of additional strains of any of these species would show very similar quinone systems, as it has been shown that the relative amounts of the major quinones for four strains of Microbacterium paraoxydans are quite stable (Buczolits et al, 2008). Strains CC-SBCK-209 T , CC-12309 T and CC-5209 T exhibited polar lipid profiles consisting of the major components diphosphatidylglycerol, phosphatidylglycerol and an unknown glycolipid that showed identical behaviour during TLC analyses of the extracts of the three strains.…”
mentioning
confidence: 99%
“…Ribotyping and methods based on whole genomes are especially recommended for the examination of whether strains belong to the same species. However, it has been shown recently for Microbacterium paraoxydans that ribotyping does not identify all strains of this species (Buczolits et al, 2008), demonstrating that, as with other fingerprinting techniques, highly similar banding patterns are useful for species identification whereas different patterns do not necessarily indicate another species. However, further standardization of these techniques is required in order to improve the reproducibility between laboratories before these methods can be proposed as alternative minimal criteria that are equivalent to DNA-DNA hybridization.…”
Section: Genomic Fingerprintingmentioning
confidence: 97%